Association between handgrip strength and raw BIA variables in adolescents aged 14-17 years - Alicante, P.; Di Gregorio, A.; Sacco, A. M.; Monfrecola, F.; Scalfi, L.; Valerio, G. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
Raw BIA (bioelectrical impedance analysis) variables such as phase angle (PhA) or impedance ratio (IR=the ratio between impedance-Z at high frequencies and Z at low frequencies), are both thought to be a proxy of muscle quality in terms of water distribution (ECW/ICW ratio), body cell mass and cellular integrity. So far, few studies have tested the relationship between handgrip strength (HGS) and body composition in adoles-cents. Our study aimed to analyze the variability in raw BIA variables and their association with HGS in 117 male (age 15.7±0.8 years, stature 171.8±7.3 cm, body weight 65.8±10.6 kg, standardized body mass in-dex=BMI-SDS +0.57±0.9) and 130 female adolescents (age 16.0±0.7 years, stature 160.8±5.6 cm, weight 57.3±8.0 kg, BMI-SDS +0.38±0.9). BIA was performed for the whole body and separately for upper limbs and lower limbs, while HGS was measured to assess the isometric strength of upper limbs. HGS was signifi-cantly correlated (r>0.500) with whole-body IR and PhA, a nd this association was even stronger with upper-limb IR and PhA. In addition, a quite strict correlation emerged between HGS and whole-body BI index at 250 kHz (index of fat-free mass). In multiple regression analysis BI indexes along with IRs or PhAs were in-dependent predictors of HGS, whereas gender and age were not. In conclusion, this study gives some infor-mation about the use of HGS and raw BIA variables in the first two decades of life, suggesting a new ap-proach to assess nutritional status in prevention and public health nutrition.